Analisis Faktor – Faktor yang Mempengaruhi Penyajian Kembali Laporan Keuangan - Chandra, Budi (Akuntansi dan Manajemen, 2020)
The purpose of this study is to examine the characteristics of the audit committee, leverage, number of subsidiaries, percentage of foreign subsidiaries, percentage of non-executive directors, expertise of the board of directors, board size, and growth on the restatement of financial statements by using company data listed on the Indonesian Stock Exchange (IDX). Using a purposive sampling method that has several criteria to collect company data from 2014-2018 and test the data with the logistic regression test method. The conclusion is that there is an influence between the size of the audit committee, the number of subsidiaries, and the percentage of non-executive directors with the restatement of financial statements. While the audit committee independence variables, audit committee meetings, audit committee expertise, leverage, percentage of foreign subsidiaries, board of directors expertise, board size, and growth do not affect the restatement of financial statements.